Managerial Tools Used in Business-Processes Re-Engineering - T. B. Temukuev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies processes and methods used in case re-engineering of business-processes at the enterprise is necessary. Forward approach to re-engineering is grounded, which identifies its several stages and highlights key characteristics of managerial tools used there. Methods of analyzing efficiency of processes taking place in creating value (product, service, work) are shown. The author traces the way from the hypothesis of the necessity of process re-engineering to analyzing the final result and checking it for compliance with the strategic plan. Key tools of managing the process are shown and their efficiency is described as applied to business-processes in oil and gas industry. The feasibility of using functional-value, plan-factorial and structural analysis is studied. The research puts forward and corroborates the hypothesis that to realize re-engineering of evolutionary and revolutionary types it is necessary to use all three mentioned above methods, as they complement each other and it is also advisory to use data gained by one method in another one. On the basis of the analysis it is possible to conclude that this system of methodology can be used in restructuring business-processes connected with marketing and innovation activity at enterprises of the fuel and power-engineering complex in Russia.